1998
DOI: 10.1074/jbc.273.13.7703
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced Association of Phospholipase Cγ1 with the G-protein-coupled AT1 Receptor

Abstract: An early event in signaling by the G-protein-coupled angiotensin II (Ang II) AT 1 receptor in vascular smooth muscle cells is the tyrosine phosphorylation and activation of phospholipase C␥1 (PLC␥1). In the present study, we show that stimulation of this event by Ang II in vascular smooth muscle cells is accompanied by binding of PLC␥1 to the AT 1 receptor in an Ang II-and tyrosine phophorylation-dependent manner. The PLC␥1-AT 1 receptor interaction appears to depend on phosphorylation of tyrosine 319 in a YIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 19 publications
2
71
1
Order By: Relevance
“…Recently, it was shown that activation of the G protein-coupled receptor, Ang II AT 1 , leads to phosphorylation of tyrosine 319 in the C-terminal intracellular domain and subsequent binding of SHP-2 phosphotyrosine phosphatase and the JAK2 tyrosine kinase complex (54). This suggests that G protein-coupled receptors possess mechanisms similar to those of cytokine and growth factor receptors for signal transduction involving cytosolic tyrosine kinases such as JAK2.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, it was shown that activation of the G protein-coupled receptor, Ang II AT 1 , leads to phosphorylation of tyrosine 319 in the C-terminal intracellular domain and subsequent binding of SHP-2 phosphotyrosine phosphatase and the JAK2 tyrosine kinase complex (54). This suggests that G protein-coupled receptors possess mechanisms similar to those of cytokine and growth factor receptors for signal transduction involving cytosolic tyrosine kinases such as JAK2.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, neither SNAP nor NAC affected the G protein-linked events leading to phospholipase C activation and increased levels of IP 3 , In other studies it was suggested that Ang II affected vascular smooth muscle cells through an association of the Ang II receptor with PLC-␥ (22) and that both PLC-␤1 and PLC-␥ were activated by Ang II in vascular smooth muscle cells (17), and EGF was shown to activate PLC-␥ in NR6 mouse fibroblasts (23).…”
Section: Discussionmentioning
confidence: 95%
“…In a subsequent study (27), these investigators discovered that the tyrosine phosphorylation was inhibited by electroporation of anti-pp60c-src antibodies into such muscle cells. Later, the same research group (28) suggested that the G-protein-coupled angiotensin II AT1 receptor can associate with intracellular proteins other than G-proteins and thereby create a signal transduction complex similar to that observed for "classic" growth factor receptors.…”
mentioning
confidence: 80%